BIBLIOMETRIC ANALYSIS OF THE INKOM JOURNAL (ANALISIS BIBLIOMETRIK JURNAL INKOM) - Koswara Natakusumah, Engkos (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
This paper proposed main problems of quantity and quality measurement of the research articles published in INKOM journal for 5 years period in informatics, computers and control system. Those three areas have become research missions of The Research Center for Informatics – Indonesia Institute of Sciences. The aim of this paper is to show how to solve research problems above using bibliometric method to analyze bibliography data available in the journal as well as to offer a summary of the research activity in the area including its most important aspects. Bibliographical data are taken from 76 articles published in the journal from May 2007 to November 2011. This paper also discusses how the method is used to measure article distribution, magazine classification category, article subject distribution, authorship patterns, and institutions distribution contributions. Results of the research show that the majority of articles are contributed by multi authors with degree of collaboration 0,553; the journal has already been widely known by the researchers outside LIPI, researchers from non-LIPI institution dominated more on the publication than from LIPI itself. The quantity of research articles increased in 2011 and used more references from scientific articles than the year before. Besides, the research quality also increased and used more cited articles from scientific journal literature than from books.